2011
DOI: 10.1103/physreve.84.036108
|View full text |Cite
|
Sign up to set email alerts
|

Dual modeling of political opinion networks

Abstract: We present the result of a dual modeling of opinion network. The model complements the agentbased opinion models by attaching to the social agent (voters) network a political opinion (party) network having its own intrinsic mechanisms of evolution. These two sub-networks form a global network which can be either isolated from or dependent on the external influence. Basically, the evolution of the agent network includes link adding and deleting, the opinion changes influenced by social validation, the political… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The semi IPN hydrogels are formed by polymerization of the acrylic monomers in water containing dissolved sodium alginate. In this IPN formation sodium alginate also takes part in the polymerization reaction by forming macro radicals [16] as shown in Fig.2a. In the semi-IPN sodium alginate remains impregnated in the crosslink network of the copolymer (Fig.2b).…”
Section: Synthesis Of Hydrogelmentioning
confidence: 98%
See 2 more Smart Citations
“…The semi IPN hydrogels are formed by polymerization of the acrylic monomers in water containing dissolved sodium alginate. In this IPN formation sodium alginate also takes part in the polymerization reaction by forming macro radicals [16] as shown in Fig.2a. In the semi-IPN sodium alginate remains impregnated in the crosslink network of the copolymer (Fig.2b).…”
Section: Synthesis Of Hydrogelmentioning
confidence: 98%
“…From this figure it is observed that sodium alginate shows absorption band at 1106 and 1025.5 cm -1 due to stretching vibration of its C-OH group and 1624 cm -1 corresponding to asymmetric stretching vibration of its carboxylate (COO -) group. The absorption band of alginate at 1417 cm -1 may be ascribed to symmetrical stretching vibration of its COO-group while the absorption band at 3351 cm -1 is due to its hydroxyl (O-H) stretching [16,20]. The FTIR of the copolymer (CP) gel is also shown in Fig at around 1398 cm -1 of the copolymer due to C-N vibration of its acrylamide moiety is also observed to shift to 1369-1396 cm -1 in the SIPNs [21].…”
Section: Ftirmentioning
confidence: 98%
See 1 more Smart Citation
“…For cylindrically symmetry, one needs some physical and geometrical conditions to be imposed. In case of regular symmetry axis (to have gravitationa collapse) one must impose the following conditions [27] (i) Existence of symmetry axis: X ≡ ξ The energy momentum tensor for such a fluid which undergoes dissipation in the form of shear viscosity and heat flow is given by [6,7] …”
Section: Interior Matter Distribution and Basic Equationsmentioning
confidence: 99%
“…For example, in an economic network formed by companies (nodes), each company has several essential features such as richness or capital, size, activity domain, age, diversity, openness and so on. In a political network composed of parties and groups, each political group has its own characteristic features, the same in the worldwide networks formed by the countries, so on and so forth.The phenomenological model of union and division has been used recently in a dual modeling of political opinion networks [18] in which union and division are two dominating events happening in the subnetwork of political parties. In present work, we are interested in knowing the behavior of a network dominated by the interplay of union/division which occurs as a function of the natures and features of the nodes.…”
mentioning
confidence: 99%